Family Support and Degree of Heart Failure in Consumption of a Low Salt Diet in Rehospitalization - Al Vieta, Angelica Lolita; Manurung, Suryani; Tarwoto, Tarwoto (JURNAL INFO KESEHATAN, 2024)
Heart failure is the most common health problem experienced by both the global and Indonesian population. Improving the quality of life of heart failure patients is paramount and depends heavily on the treatment undertaken. The number of relapses that result in re-hospitalization of heart failure patients indicates a lack of adherence to therapy. Some of the risk factors for re-hospitalization of heart failure are age, gender, degree of disease, and comorbidities. Non-compliance with medication therapy, excessive physical activity, non-adherence to medical care, failure to recognize clinical manifestations of heart failure, and violation of low-salt dietary restrictions will result in rehospitalization due to recurrence. Patients without family members may have higher non-compliance, as they lack the support needed to change their behavior. The purpose of this study was to analyze the relationship between family support and the degree of heart failure disease in consuming a low salt diet on the incidence of re-hospitalization. This research design uses a cross-sectional design of analytic survey research. The population of this study were heart failure patients who sought treatment at Pasar Rebo Hospital with a sample of 75 people. Sampling using purposive sampling. Data analysis using univariate and bivariate tests. In this study, there is a relationship between family support in the consumption of a low-salt diet on the incidence of re-hospitalization based on the degree of disease. The results of the bivariate test (Person Chi-Square) showed that there was a significant relationship between family support in the consumption of a low-salt diet and the incidence of re-hospitalization for heart failure (p<0.05). In this study it was found that there was a significant relationship between family support and the degree of heart failure in consuming a low salt diet in the event of re-hospitalization, Most of the respondents' degree of heart failure re-hospitalization were in class I and class II degrees of disease as many as 72 (96%) and class I and II degrees of disease were in emotional family support, information and appreciation 5-14 (15-62%) Researchers suggest that future researchers can add patient respondents who experience re-hospitalization for heart failure.